Synergistic effects of quercetin and regular exercise on the recovery of spatial memory and reduction of parameters of oxidative stress in animal model of Alzheimer's disease - Molaei, Amin; Hatami, Homeira; Dehghan, Gholamreza; Sadeghian, Reihaneh; Khajehnasiri, Nazli (EXCLI journal, 2020)
It has widely been reported that the brain in Alzheimer's disease (AD) is affected by increased oxidative stress, and this may have a role in the pathogenesis of this disorder. Quercetin, a polyphenol extensively found in nature, has recently been considered. Also, physical activities have a paradoxical effect on brain function in older adults. Therefore, this study aimed at investigating the synergic effects of quercetin (as chemical treatment) and exercise (as physical treatment) on AD-induced learning and memory impairment. Fifty-six adult male Wistar rats were randomly assigned into one of the following eight groups (n=7): The Control, Sham (saline), AD (intracerebroventricular administration of streptozotocin (STZ)), AD+80 mg/kg Quercetin (STZ+Q80), Quercetin vehicle (1 % Ethanol)+STZ, Exercise pretreatment (EX)+STZ, Off the treadmill+STZ, and EX+Q80+STZ. Quercetin administration was done intraperitoneally for 21 days after STZ injection. The rats ran on the treadmill for one hour a day for 60 days at a speed of 20-22 m/min. After the treatment, the spatial memory and levels of oxidative stress parameters were evaluated. The results showed that STZ caused spatial memory impairment and increased oxidative stress in the hippocampus. Exercise pretreatment or Quercetin injection improved the spatial memory impairment and oxidative stress caused by STZ injection. However, the combination of quercetin and exercise pretreatment was more effective. It can be concluded that the combined exercise pretreatment and Quercetin injection affected the antioxidant defense system and improved STZ-induced memory impairment.